Carbon-doped titanium dioxide composite photocatalyst and its preparation method and application

By doping carbon, carbon-doped titanium dioxide composite photocatalyst is prepared, which solves the problem of insufficient activity of traditional photocatalytic materials under natural light and indoor light conditions, and achieves efficient sterilization and deodorization effects under visible light.

CN119733495AInactive Publication Date: 2025-04-01INNER MONGOLIA SAN ZHONG TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510227804.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-28
Publication Date
2025-04-01
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional titanium dioxide photocatalytic materials exhibit high photocatalytic activity only under ultraviolet light, limiting their practical application in natural and indoor light conditions.

Method used

By doping carbon, a carbon-doped titanium dioxide composite photocatalyst is prepared, which broadens its light absorption range to the visible light region (400-800 nm), and optimizes the specific surface area and pore structure of the material.

Benefits of technology

It has achieved efficient killing of bacteria and viruses under visible light conditions, with a bactericidal rate of more than 99%, and can quickly decompose volatile organic matter and odor molecules, significantly improving photocatalytic performance and getting rid of the limitations of ultraviolet light.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119733495A_ABST
    Figure CN119733495A_ABST
Patent Text Reader

Abstract

The present invention relates to a carbon-doped titanium dioxide composite photocatalyst and a preparation method and application thereof, and relates to the field of chemical technology, comprising the following steps: (1) mixing sodium acetate and glacial acetic acid to obtain a precursor solution; (2) mixing the precursor solution with butyl titanate, and then adding chitosan, and mixing them evenly to obtain a mixed solution; (3) subjecting the mixed solution to a hydrothermal reaction at a temperature below 200° C. to obtain a carbon-doped titanium dioxide composite photocatalyst. The free radicals generated by the carbon-doped titanium dioxide composite photocatalyst under visible light excitation can continuously decompose bacteria, viruses and odor molecules in the air, and have good reusability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of chemical technology, and in particular to a carbon-doped titanium dioxide composite photocatalyst and a preparation method and application thereof. Background Art

[0002] Indoor pollution is mainly caused by the presence of various volatile organic compounds in indoor air that pollute the indoor environment. The most harmful ones are radon, formaldehyde, benzene, ammonia, esters, trichloroethylene, etc. Indoor environmental pollution has become a major issue affecting people's physical health and safety. As a key area in public and private spaces, the environmental sanitation of toilets directly affects people's quality of life and health. Since the toilet environment is usually humid and the ventilation conditions are limited, it is very easy to breed bacteria and viruses, such as pathogenic microorganisms such as Escherichia coli and Staphylococcus aureus. These microorganisms may cause cross-infection, especially in crowded public places such as hospitals and schools. Toilets often release volatile organic compounds (VOCs), such as ammonia and hydrogen sulfide, which not only have odors, but also pose a potential threat to human health. Long-term exposure to volatile compounds may cause respiratory diseases, headaches, and even more serious health problems.

[0003] In recent years, photocatalytic technology has attracted widespread attention due to its excellent bactericidal ability and environmental protection characteristics. As a classic photocatalytic material, it is widely used in air purification and water treatment due to its chemical stability, non-toxicity and low price. High photocatalytic activity is exhibited only under ultraviolet light (wavelength < 400 nm), which limits its practical application under natural light and indoor light conditions.

[0004] To overcome the above limitations, researchers proposed to improve In view of this, the present invention provides a carbon-doped titanium dioxide composite photocatalyst and a preparation method and application thereof. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a carbon-doped titanium dioxide composite photocatalyst and its preparation method and application. The purpose is to use the carbon-doped titanium dioxide composite photocatalyst for sterilization and / or removal of toxic gases in indoor environments by utilizing its excellent visible light response ability and high-efficiency sterilization and deodorization properties.

[0006] The technical solution of the present invention to solve the above technical problems is as follows: In a first aspect, a method for preparing a carbon-doped titanium dioxide composite photocatalyst comprises the following steps: (1) mixing sodium acetate and glacial acetic acid to obtain a precursor solution; (2) mixing the precursor solution with butyl titanate, adding chitosan, and mixing well to obtain a mixed solution; (3) subjecting the mixed solution to a hydrothermal reaction at a temperature below 200° C. to obtain a carbon-doped titanium dioxide composite photocatalyst; In step (2), the chitosan accounts for 2%-5% of the mass of the butyl titanate; The light absorption wavelength range of the carbon-doped titanium dioxide composite photocatalyst is 400 nm-800 nm, and the effective band gap energy of the carbon-doped titanium dioxide composite photocatalyst is 2.8 eV-3.0 eV; The carbon-doped titanium dioxide composite photocatalyst comprises nano-scale titanium dioxide particles and a carbon layer, wherein the nano-scale titanium dioxide particles are uniformly distributed on the carbon layer, the particle size of the nano-scale titanium dioxide particles is less than 50 nm, and the specific surface area is 150 m² / g-200 m² / g.

[0007] Principle: The free radicals generated by the carbon-doped titanium dioxide composite photocatalyst under the excitation of visible light can continuously decompose bacteria, viruses and odor molecules in the air and have good reusability.

[0008] The beneficial effects of the present invention are: (1) High efficiency: The present invention can broaden the The light absorption range of the photocatalyst can be extended to the visible light region (wavelength 400-800 nm); it can effectively inhibit the rapid recombination of photogenerated electron-hole pairs, thereby significantly improving its photocatalytic efficiency; it can also optimize the specific surface area and pore structure of the material, and further enhance the adsorption and degradation capabilities of volatile organic compounds and bacteria; therefore, the carbon-doped titanium dioxide composite photocatalyst of the present invention can effectively kill common pathogens such as Escherichia coli and Staphylococcus aureus under visible light conditions, with a sterilization rate of more than 99%, and can quickly decompose volatile organic compounds (VOCs, such as ammonia and hydrogen sulfide) and odor molecules in toilet environments, thereby achieving a deodorizing effect and getting rid of the limitations of ultraviolet light.

[0009] (2) Simple process flow: The carbon-doped titanium dioxide composite photocatalyst of the present invention is synthesized by a one-pot hydrothermal method, which does not require high-temperature calcination, thus avoiding the particle agglomeration and phase change problems caused by high temperature and maintaining long-term stability; it also does not require the addition of toxic reagents, and the material itself is non-toxic and harmless and environmentally friendly.

[0010] (3) Long material life and high economic efficiency: The carbon-doped titanium dioxide composite photocatalyst of the present invention can be recycled for many times without obvious attenuation of photocatalytic performance and is highly economical.

[0011] Based on the above technical solution, the present invention can also be improved as follows.

[0012] Furthermore, in step (1), the ratio of the sodium acetate to the glacial acetic acid is (1.0-1.5) g: (5-10) mL.

[0013] The beneficial effect of adopting the above further scheme is: ensuring the efficient progress of the reaction and avoiding incomplete reaction or generation of by-products due to excess or deficiency.

[0014] Furthermore, step (2) includes the following specific steps: adding butyl titanate dropwise into the precursor solution and mixing evenly, and then adding chitosan and mixing evenly to obtain a mixed solution.

[0015] The beneficial effect of adopting the above further scheme is that the uniform mixing of butyl titanate and chitosan helps to form a uniform composite material structure. By adjusting the amount of chitosan added, the carbon doping content can be effectively controlled, thereby adjusting the surface characteristics and photocatalytic performance of the photocatalyst.

[0016] Furthermore, the parameters of the hydrothermal reaction in step (3) are: temperature of 180° C. and time of 8 h-24 h.

[0017] The beneficial effect of adopting the above further scheme is: through experiments, it was found that excessively high temperature (over 200°C) will cause the titanium dioxide particle size to increase, thereby reducing the specific surface area and photocatalytic efficiency, while insufficient reaction time, less than 8 hours, will not form a stable carbon-doped layer; therefore, the reaction conditions of 180°C and 8 h-24 h can effectively balance the particle size, specific surface area and photocatalytic performance of the material.

[0018] In a second aspect, a carbon-doped titanium dioxide composite photocatalyst is prepared by the preparation method.

[0019] The beneficial effects of adopting the above scheme are: the carbon-doped titanium dioxide composite photocatalyst of the present invention can continuously decompose bacteria, viruses and odor molecules in the air, and has good reusability. Through carbon doping, the energy band width of titanium dioxide is reduced, and the light absorption range is expanded to the visible light region. The introduction of the carbon layer optimizes the surface structure of the material, forming abundant pores, and effectively improving the adsorption capacity of pollutants; the interface effect between the carbon layer and titanium dioxide helps to improve the separation efficiency of photogenerated electrons and holes, and significantly enhances the photocatalytic performance of the material. Titanium dioxide particles are distributed on the carbon layer, with a particle size of less than 50 nanometers and a specific surface area of ​​150 m² / g-200 m² / g, and have good photocatalytic reaction activity.

[0020] In a third aspect, the application of the carbon-doped titanium dioxide composite photocatalyst is to use the carbon-doped titanium dioxide composite photocatalyst for sterilization and / or removal of toxic gases in indoor environments.

[0021] Furthermore, the toxic gas includes at least one of formaldehyde, ammonia, sulfide and nitrogen oxide.

[0022] Furthermore, the carbon-doped titanium dioxide composite photocatalyst is used for sterilization and / or deodorization in toilet environments.

[0023] The carbon-doped titanium dioxide composite photocatalyst is coated on the inner surface of the toilet or integrated into the toilet ventilation device or air purification equipment to be used for sterilization and / or deodorization of the toilet.

[0024] Coating on the inner surface of the toilet, specifically including: evenly coating the carbon-doped titanium dioxide composite photocatalyst on the toilet wall, toilet surface or sewer inner wall, and continuously exerting the sterilization and deodorization effect under natural light or indoor lighting conditions; integrated into the toilet ventilation device or air purification equipment, specifically including: combining the photocatalyst with the ventilation equipment, and using the built-in light source (such as LED light) to stimulate the photocatalyst to degrade pathogens and odor molecules in the air; by designing modular photocatalyst components, it is convenient for flexible installation and replacement in home toilets, public toilets or mobile toilets. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The XRD test diagram of the present invention; wherein a is a pure titanium dioxide sample, b, c, d correspond to titanium dioxide samples doped with 2%, 3%, and 5% chitosan, respectively; Figure 2 This is a SEM test image of a titanium dioxide sample containing 5% chitosan of the present invention; wherein the size of A is 18 μm, and the size of B is 100 nm; Figure 3 This is the EDS test chart of the titanium dioxide sample containing 5% chitosan of the present invention; Figure 4 The UV-Vis spectra of the present invention; wherein a is a pure titanium dioxide sample, b, c, and d correspond to titanium dioxide samples doped with 2%, 3%, and 5% chitosan, respectively; Figure 5 The XPS graph of the titanium dioxide sample containing 5% chitosan of the present invention; wherein A is the spectrum of C1s, showing the information of carbon element; B is the spectrum of O1s, showing the information of oxygen element; C is the high-resolution spectrum of Ti2p, showing the detailed information of titanium element; Figure 6 The graph is a comparison of the degradation curves of methylene blue of the carbon source-doped titanium dioxide powder under simulated sunlight; wherein, a is a pure titanium dioxide sample, and b, c, and d correspond to titanium dioxide samples doped with 2%, 3%, and 5% chitosan, respectively. DETAILED DESCRIPTION

[0026] The principles and features of the present invention are described below, and the examples are only used to explain the present invention and are not used to limit the scope of the present invention. If no specific technology or conditions are specified in the embodiments, the technology or conditions described in the literature in this field or the product instructions are used. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased through regular channels.

[0027] Example 1. Preparation of carbon-doped titanium dioxide composite photocatalyst.

[0028] This embodiment relates to a method for preparing a carbon-doped titanium dioxide composite photocatalyst, comprising the following steps: (1) Sodium acetate (Shanghai Aladdin Biochemical Technology Co., Ltd.) and glacial acetic acid (Shanghai MacLean Biochemical Technology Co., Ltd.) were mixed to obtain a precursor solution; (2) mixing the precursor solution with butyl titanate (Shanghai MacLean Biochemical Technology Co., Ltd.), and then adding chitosan (Shanghai Aladdin Biochemical Technology Co., Ltd.), and mixing well to obtain a mixed solution; (3) subjecting the mixed solution to a hydrothermal reaction at a temperature below 200° C. to obtain a carbon-doped titanium dioxide composite photocatalyst; The light absorption wavelength range of the carbon-doped titanium dioxide composite photocatalyst is 400 nm-800 nm, and the effective band gap energy of the carbon-doped titanium dioxide composite photocatalyst is 2.8 eV-3.0 eV.

[0029] In this embodiment, the ratio of the sodium acetate to the glacial acetic acid in step (1) is preferably (1.0-1.5) g: (5-10) mL, for example, 1.0 g: 10 mL, 1.2 g: 8 mL, 1.5 g: 10 mL, etc.

[0030] In this embodiment, step (2) includes the following specific steps: adding butyl titanate dropwise to the precursor solution and mixing evenly, then adding chitosan and mixing evenly to obtain a mixed solution.

[0031] In this embodiment, the chitosan in step (2) accounts for 0.5%-10% of the mass of the butyl titanate, such as 0.5%, 2%, 3%, 5%, 10%, etc., and further preferably, the chitosan accounts for 2%-5% of the mass of the butyl titanate, such as 2%, 3%, 5%, etc. The volume ratio of the precursor solution to the butyl titanate in step (2) is not particularly limited as long as it meets the requirements.

[0032] In this embodiment, the parameters of the hydrothermal reaction in step (3) are: temperature of 180° C., time of 8 h-24 h, for example, 8 h, 10 h, 12 h, 16 h, 24 h, etc.

[0033] This embodiment includes the following specific steps: Step 1: First, weigh 1.10 g of sodium acetate and gradually add it to 10 mL of glacial acetic acid, and continue stirring at room temperature until the solution is completely transparent and a uniform precursor solution is formed. By combining gradual addition with continuous stirring, the uniformity and chemical stability of the solution are ensured, providing a high-quality precursor liquid environment for subsequent reactions; Step 2, slowly add 5 mL of butyl titanate to the precursor solution prepared in step 1 at a rate of 1 drop per second, and continue stirring for 10 minutes under vigorous stirring conditions; the combination of slow dripping and rapid stirring ensures uniform dispersion of butyl titanate molecules in the solution to avoid precipitation caused by excessive local concentration; Step 3, according to the requirements of the carbon content in the target composite catalyst, a predetermined mass of chitosan is added to the mixed solution obtained in step 2; the amount of chitosan added is 0, 2%, 3% and 5%; chitosan is a green and environmentally friendly carbon source, and the specific surface area and pore distribution of the photocatalyst material are significantly improved by adjusting the addition ratio; after adding chitosan, stirring is continued at room temperature for 1 hour to ensure that the chitosan is completely dissolved and fully mixed with the solution.

[0034] Step 4, transferring the mixed solution obtained in step 3 to a stainless steel autoclave lined with polytetrafluoroethylene; after ensuring that the autoclave cover is well sealed, placing it in a heating device; the hydrothermal reaction is carried out at 180° C. for 12 hours, and the reaction temperature and time are selected to ensure the full growth of titanium dioxide crystals while avoiding the problem of particle agglomeration caused by high temperature; during the reaction process, the solution undergoes a series of chemical reactions to form a preliminary carbon-modified titanium dioxide composite; Step 5: After the reaction is completed, the autoclave is removed from the heating device and cooled to room temperature. The product is separated from the reaction solution by centrifugation; then, the product is washed with deionized water and anhydrous ethanol three times each time to remove residual reactants and impurities; after each washing, the solid product is recovered again by centrifugation.

[0035] Step 6, placing the washed solid product in a vacuum drying oven and drying it at 60° C. for 24 hours; after drying, a carbon-doped titanium dioxide composite photocatalyst is obtained; the product can be directly used in photocatalytic experiments.

[0036] 2. Test methods and measurement results.

[0037] 2.1 XRD test.

[0038] XRD tests were performed on the photocatalytic material titanium dioxide and its chitosan-doped titanium dioxide samples (i.e., carbon-doped titanium dioxide composite photocatalysts). The results are as follows: Figure 1As shown, a is a pure titanium dioxide sample, b, c, and d correspond to titanium dioxide samples doped with 2%, 3%, and 5% chitosan, respectively.

[0039] Figure 1 The results show that the spectra of a, b and c all correspond to anatase titanium dioxide (JCPDS No. 21-1272) with photocatalytic activity, and no other impurities are detected, which indicates that the doping process has good process stability. The spectrum of d shows that there may be a mixed phase of anatase titanium dioxide (JCPDS No. 21-1272) and a small amount of rutile titanium dioxide (JCPDS No. 21-1276).

[0040] The grain size was calculated from the half-peak width of the spectrum using the Scherrer formula: the grain size of the pure titanium dioxide sample (a) is about 9.4 nm, the grain size of the sample doped with 2% chitosan (b) is 11.9 nm, the grain size of the sample doped with 3% chitosan (c) is 12.2 nm, and the grain size of the sample doped with 5% chitosan is about 20~30 nm. These results show that as the chitosan doping concentration increases, the sample grain size gradually increases, which may be due to the release of lattice strain caused by doping or the influence of crystal growth.

[0041] 2.2 SEM test.

[0042] The synthesized carbon source doped titanium dioxide powder was tested by SEM, and the results are as follows Figure 2 As shown in A and B. Figure 2 From A and B in the figure, it can be seen that the particles of carbon-doped titanium dioxide show a more obvious agglomeration phenomenon, and the particles are connected to each other to form an irregular cluster structure. The shape of the particles is mostly irregular polyhedron, the surface is relatively rough, there are certain unevenness and fine particles attached. The size distribution of the particles is relatively uniform, but there are certain size differences. Most of the particles have a diameter of about 10 microns, and some particles may be slightly larger or smaller than this size. Overall, the microstructure of the material is relatively dense, and the particles are tightly bonded. This structure may help to increase the specific surface area and catalytic activity of the material.

[0043] 2.3 EDS test.

[0044] like Figure 3 As shown by Figure 3It can be seen that in the carbon distribution map, the yellow bright spots are evenly distributed, indicating that carbon is evenly doped in titanium dioxide. In the oxygen distribution map, the green bright spots are also evenly distributed, indicating that oxygen is well distributed. In the titanium distribution map, the yellow bright spots are also evenly distributed, indicating that carbon doping has not destroyed the basic structure of titanium dioxide. By comparing the scale and color intensity of the three pictures, carbon, oxygen and titanium are evenly distributed in the EDS map of carbon-doped titanium dioxide, indicating that the carbon doping process is effective and uniform, which helps to maintain the structure and properties of the material.

[0045] 2.4 UV-Vis ultraviolet-visible-infrared diffuse reflectance spectrum test.

[0046] Figure 4 The UV-Vis spectrum shows the effect of chitosan doping on the light absorption properties of titanium dioxide, where a, b, c, and d represent pure titanium dioxide, 2% chitosan doped, 3% chitosan doped, and 5% chitosan doped titanium dioxide samples, respectively. The results show that after doping with chitosan, the absorption spectrum of titanium dioxide is significantly red-shifted, indicating that the band gap energy is reduced, which significantly enhances the material's absorption capacity for visible light. At the same time, with the increase in the chitosan doping ratio (from b to d), the absorption intensity of the sample in the visible light region gradually increases, especially the 5% chitosan doped sample shows the strongest absorption effect. This phenomenon may be attributed to the introduction of chitosan, which changes the electronic structure and surface properties of titanium dioxide, thereby significantly improving its optical properties.

[0047] 2.5 XPS graph.

[0048] Figure 5 This is the XPS image of the prepared carbon source doped titanium dioxide powder. Figure 5 In Figure A, the C1s spectrum shows an obvious peak near 284.80 eV, corresponding to the CC bond. The peaks near 285.9 eV and 289.6 eV correspond to CO and C=O bonds, respectively, which shows that carbon not only exists in CC bonds in titanium dioxide, but also forms CO and C=O bonds with oxygen, indicating that carbon is doped into the titanium dioxide lattice. Figure 5 Figure 1. B, O1s spectrum. The main peak is at 530.90 eV, corresponding to the Ti-O bond. The smaller peak near 532.39 eV may be the signal of the CO bond, which further confirms that carbon forms a chemical bond with oxygen and that carbon doping affects the chemical environment of oxygen. Figure 5 C in the figure is the peaks of Ti2p at 459.74 eV and 465.43 eV, respectively. and , the positions and intensities of these peaks look relatively standard, indicating that the chemical state of titanium has not changed significantly due to carbon doping. Overall, carbon doping successfully introduced new chemical bonds and changed the chemical environment of oxygen, but had little effect on the chemical state of titanium. This may affect the photoelectric properties or other physical and chemical properties of titanium dioxide.

[0049] 2.6 Degradation of methylene blue.

[0050] Figure 6 This is the degradation curve of methylene blue by the prepared carbon source doped titanium dioxide powder under simulated sunlight; Figure 6 The effect of carbon-doped titanium dioxide on the degradation of methylene blue is shown, where a is pure undoped titanium dioxide, b, c, and d represent 2%, 3%, and 5% chitosan-doped titanium dioxide samples, respectively. As can be seen from the figure, the higher the doping ratio, the stronger the degradation performance of titanium dioxide, which is reflected in the change of C / C over time. 0 The value decreased more significantly. Among them, the 5% doped sample (d) showed the best degradation effect within 120 minutes, almost completely degrading methylene blue, while the undoped sample (a) had the worst degradation effect. This shows that chitosan doping can significantly improve the photocatalytic performance of titanium dioxide, and the increase in doping ratio further enhances the catalytic efficiency, but it should be noted that there may be a performance optimization limit caused by excessive doping.

[0051] 2.7 Antibacterial performance test.

[0052] According to WS / T 650-2019 "Evaluation Methods for Antibacterial and Antimicrobial Effects", the antibacterial properties of chitosan-doped titanium dioxide were tested. The results are shown in Table 1.

[0053] Table 1 Among them, a is undoped pure titanium dioxide, b is 2% chitosan-doped titanium dioxide, c is 3% chitosan-doped titanium dioxide, d is 5% chitosan-doped titanium dioxide, and the test strains include Escherichia coli (8099), Staphylococcus aureus (ATCC 6538) and Candida albicans (ATCC 10231). The tests were carried out at different time intervals (15 days and 30 days).

[0054] 2.8 Antibacterial performance test.

[0055] The deodorizing performance of chitosan doped with titanium dioxide was tested. The experiment selected common toilet odor sources, including ammonia (urine odor), hydrogen sulfide (corruption odor) and indole (feces odor). The test used odor source solutions of different concentrations, and after acting in a closed environment for 5 minutes, the test was evaluated by the subjective scoring of the subjects. Refer to Table 2 for scoring. The results are shown in Table 3.

[0056] Table 2 Table 3 2.9 Cyclic experimental testing.

[0057] Experimental design: Sample b (2% chitosan-doped titanium dioxide, low concentration), sample c (3% chitosan-doped titanium dioxide, medium concentration) and sample d (5% chitosan-doped titanium dioxide, high concentration) were selected for the cycle experiment.

[0058] Experimental steps: In each cycle, the corresponding samples were placed in a closed environment and odor source solutions (ammonia, hydrogen sulfide and indole) of the same concentration were added. After 5 minutes of exposure, the samples were evaluated by subjective scoring, and the scoring criteria were as shown in Table 2.

[0059] The score after each cycle was recorded, and 5 cycles were performed in total.

[0060] Table 4 Result analysis: It can be seen from Table 4 that the scores of samples b, c, and d remain roughly unchanged after 5 cycles, indicating that the antibacterial performance of chitosan-doped titanium dioxide has not decreased significantly after multiple uses, and it has good recycling performance and is suitable for repeated use in practical applications.

[0061] 3. Application examples.

[0062] 3.1 Removal of toilet odor.

[0063] The prepared carbon-modified titanium dioxide composite catalyst (5% chitosan-doped titanium dioxide, C- ) is applied to the toilet vents or wall tile surfaces and used under light conditions. The carbon-modified titanium dioxide composite catalyst can catalytically decompose odorous gases such as ammonia and hydrogen sulfide in the air under natural light or indoor light, reducing the concentration of odor. After a period of use, the odor in the toilet environment is significantly reduced and the air quality is significantly improved.

[0064] 3.2 Antibacterial function of toilet surface.

[0065] Carbon modified titanium dioxide composite catalyst (5% chitosan doped titanium dioxide, C- ) is sprayed on frequently touched surfaces in toilets (such as toilet seats, sinks, door handles), and can be irradiated with ultraviolet or visible light to continuously inhibit the growth of bacteria and viruses. Experiments have shown that the number of bacteria on the sprayed surfaces is reduced by more than 90% within 72 hours, achieving a long-lasting antibacterial effect. In public toilets, regular re-spraying of the catalyst layer can further improve the quality of environmental hygiene and reduce the risk of cross-infection.

[0066] 3.3 Optimization of toilet sewage treatment effect.

[0067] The carbon-modified titanium dioxide composite catalyst (5% chitosan-doped titanium dioxide, C- ) is added to the toilet sewage discharge system in powder form, and the strong oxidation effect of the catalyst under light conditions is used to effectively decompose the organic pollutants (such as urea, ammonia nitrogen, etc.) in the sewage. The treated sewage discharge meets national standards and effectively reduces pollution to the environment. Sewage treatment equipment using carbon-modified titanium dioxide composite catalyst can achieve efficient treatment at low energy consumption, which is very suitable for toilet sewage treatment systems in densely populated areas.

[0068] 3.4 Toilet humidity control and mold prevention.

[0069] The photocatalytic coating is installed on the toilet ceiling or wall, and the carbon-modified titanium dioxide composite catalyst (5% chitosan-doped titanium dioxide, C- ) Decompose organic matter and mold spores in moisture under light conditions, reduce humidity levels and prevent mold growth. This method is particularly suitable for public toilets and home bathrooms in high humidity areas. In practical applications, the coating can be replaced or replenished regularly according to humidity and mold growth conditions to ensure long-term effect.

[0070] 3.5 Used in combination with toilet air equipment.

[0071] Carbon modified titanium dioxide composite catalyst (5% chitosan doped titanium dioxide, C- ) is integrated into the filter of the toilet air purifier. When the device is running, the air passes through the filter coated with the catalyst, and the odor molecules and harmful gases are decomposed into harmless small molecules (such as and ), continuously purifying the air in the toilet. Tests have shown that the use of an air purifier containing a carbon-modified titanium dioxide composite catalyst filter has reduced the concentration of hydrogen sulfide in the air in the toilet by more than 85%, while volatile organic compounds (VOCs) have also been significantly reduced, further improving the toilet experience.

[0072] 3.6 Intelligent toilet system.

[0073] The carbon-modified titanium dioxide composite catalyst (5% chitosan-doped titanium dioxide, C- ) is used in the intelligent photocatalytic system of toilets. The system can automatically adjust the light intensity according to the real-time detected air quality and humidity, thereby optimizing the photocatalytic efficiency of the catalyst. This system is suitable for high-flow public toilets and can continuously keep the toilet environment fresh and hygienic, while reducing energy consumption and improving overall management efficiency.

[0074] In summary, the present invention can broaden the The light absorption range of the photocatalyst can be extended to the visible light region (wavelength 400-800 nm); it can effectively inhibit the rapid recombination of photogenerated electron-hole pairs, thereby significantly improving its photocatalytic efficiency; it can also optimize the specific surface area and pore structure of the material, and further enhance the adsorption and degradation capabilities of volatile organic compounds and bacteria; therefore, the carbon-doped titanium dioxide composite photocatalyst of the present invention can effectively kill common pathogens such as Escherichia coli and Staphylococcus aureus under visible light conditions, with a sterilization rate of more than 99%, and can quickly decompose volatile organic compounds (VOCs, such as ammonia and hydrogen sulfide) and odor molecules in the toilet environment, thereby achieving a deodorizing effect and getting rid of the limitations of ultraviolet light.

[0075] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for preparing a carbon-doped titanium dioxide composite photocatalyst, characterized in that: The steps include: (1) mixing sodium acetate and glacial acetic acid to obtain a precursor solution; (2) mixing the precursor solution with butyl titanate, adding chitosan, and mixing well to obtain a mixed solution; (3) subjecting the mixed solution to a hydrothermal reaction at a temperature below 200° C. to obtain a carbon-doped titanium dioxide composite photocatalyst; In step (2), the chitosan accounts for 2%-5% of the mass of the butyl titanate; The light absorption wavelength range of the carbon-doped titanium dioxide composite photocatalyst is 400 nm-800 nm, and the effective band gap energy of the carbon-doped titanium dioxide composite photocatalyst is 2.8 eV-3.0 eV; The carbon-doped titanium dioxide composite photocatalyst comprises nano-scale titanium dioxide particles and a carbon layer, wherein the nano-scale titanium dioxide particles are uniformly distributed on the carbon layer, the particle size of the nano-scale titanium dioxide particles is less than 50 nm, and the specific surface area is 150 m² / g-200 m² / g.

2. The method for preparing the carbon-doped titanium dioxide composite photocatalyst according to claim 1, characterized in that: The usage ratio of the sodium acetate to the glacial acetic acid in step (1) is (1.0-1.5) g: (5-10) mL.

3. The method for preparing the carbon-doped titanium dioxide composite photocatalyst according to claim 1, characterized in that: Step (2) includes the following specific steps: adding butyl titanate dropwise into the precursor solution and mixing evenly, then adding chitosan and mixing evenly to obtain a mixed solution.

4. The method for preparing the carbon-doped titanium dioxide composite photocatalyst according to any one of claims 1 to 3, characterized in that: The parameters of the hydrothermal reaction in step (3) are: temperature of 180° C. and time of 8 h-24 h.

5. Carbon-doped titanium dioxide composite photocatalyst, characterized in that: The carbon-doped titanium dioxide composite photocatalyst is prepared by the preparation method according to any one of claims 1 to 4.

6. Application of carbon-doped titanium dioxide composite photocatalyst, characterized in that: The carbon-doped titanium dioxide composite photocatalyst described in claim 5 is used for sterilization and / or removal of toxic gases in indoor environments.

7. The use of the carbon-doped titanium dioxide composite photocatalyst according to claim 6, characterized in that: The toxic gas includes at least one of formaldehyde, ammonia, sulfide and nitrogen oxide.

8. The use of the carbon-doped titanium dioxide composite photocatalyst according to claim 6, characterized in that: The carbon-doped titanium dioxide composite photocatalyst is used for sterilization and / or deodorization in toilet environments.

Citation Information

Patent Citations

  • Visible light response cobalt-doped anatase TiO2 mesocrystal, and preparation method and photocatalytic application thereof

    CN103586027A

  • Carbon-atom-doped titanium dioxide photocatalyst and preparation method thereof

    CN105536763A

  • Preparation of CS-Cu / titanium dioxide nanocomposite material and application thereof in photocatalytic reduction of carbon dioxide

    CN108855228A